Split Letters Prefixing Quranic Chapters: An Interpretive Study - Adel Ali Al-Shddy (Journal of Islamic Studies, 2009)
The study handles a case that is object of different scholars' opinions, a difference that in many times reaches the extent of contradiction. The reason behind the discrepancy emerges in the first place due to their disagreement on how to regard the Arabic split letters that prefix some Quranic chapters, namely whether they belong to the ''Muhkam” , the meaning of which is judged, firm and decisive, , or to the "Mutashabih" (permitting many facets of interpretation, and their actual meaning is not known exactly). The study highlights the importance of this topic, since these letters belong to the Quran, which Allah ordered to ponder on, to interpret and to understand. In addition, some of these letters constitute a complete verse, sometimes even two, and for eloquent people, the beginning of a text draws the attention to its content and points to its purpose. The statements reported from many of the early Muslims "Salat", including a group of Prophet Muhammad's companions (Sahaba), in what concerns these split letters indicate the importance of posing the issue; not to mention the many irrational and illogical arguments interpreting the meaning of these letters, and which can only be repelled though study of the case. A noticeable point in this case is the variant opinions of the scholars with regard to the meaning of the split letters; whereas some deemed them as "Mutashabih" which only Allah knows the meaning of others claimed that they epresent names of Allah or of the Quran or of some of its chapters and sections. A third group went too far in believing that they are symbols for words in other non-Arabic languages like the Hieroglyphs, or refer to certain events using some arithmetical calculations_ In the first chapter, which comprises eight subjects, the researcher details all these opinions and highlights the strong and weak sides in each of them. Another point of discussion that the researcher was keen to put forth was the fact that some people confuse the opinions related to the meaning of the split letters with those interpreting the reason and secret behind beginning some Quranic chapters with these letters. For this point, the researcher dedicated a chapter constituting seven subjects, which handle the challenge, the inimitability and the differentiation between the Quranic chapters, in addition to inciting people to listen to the Quran and demonstrating the linguistic and thematic wondrous nature of the Quran. The researcher concluded his study by summing up the most preponderant opinion with regard to the meaning and the purpose of the split letters at the beginning of the Quranic chapters.